Tapered multicore fibers for energy-scalable fiber laser systems - Aleshire Christopher; Steinkopff Albrecht; Klenke Arno; Jauregui Cesar; Böhme Steffen; Koch Tobias; Kuhn Stefan; Nold Johannes; Haarlammert Nicoletta; Schreiber Thomas; Limpert Jens (EPJ Web of Conferences, 2022)
With active multicore fibers (MCFs), many parallel amplifying waveguides can be densely assembled into a common glass cladding. A tapered fiber geometry applied to MCFs enhances the power and energy scalability of these systems by increasing the doped waveguide volume and reducing peak irradiance while maintaining low output mode order. Recent high-energy experiments have achieved 37 mJ ns-class pulse energies with Yb-doped tapered MCFs, with potential application to a new generation of compact MCF-based coherently-combined laser systems. In this submission, latest experimental results with tapered MCFs and flexible fabrication of taper profiles as a post-draw processing step will be discussed. Numerical analyses of MCF tapers will be presented, using beam propagation method (BPM) and mode-decomposition techniques to study mode coupling and inter-core crosstalk. These simulations are used to guide the tapering of existing fibers and aid the design of future “taper-ready” MCFs.